Clinical spectrum of ischaemic arterial diseases associated with COVID-19: a series of four illustrative cases. Issue 1 (25th December 2020) - Guillet, Henri; Gallet, Romain; Pham, Vincent; D'Humières, Thomas; Huguet, Raphaelle; Lim, Pascal; Michel, Marc; Khellaf, Mehdi
Abstract: Background: Severe coronavirus-induced disease 2019 (COVID-19) leads to acute respiratory distress syndrome with an increased risk of venous thrombo-embolic events. To a much lesser extent, arterial thrombo-embolic events have also been reported in this setting. Case summary: Here, we describe four different cases of COVID-19 infection with ischaemic arterial events, such as a myocardial infarction with high thrombus load, ischaemic stroke on spontaneous thrombosis of the aortic valve, floating thrombus with mesenteric, splenic and renal infarction, and acute limb ischaemia. Discussion: Cardiovascular risk factors such as hypertension, obesity, and diabetes are comorbidities most frequently found in patients with a severe COVID-19 infection and are associated with a higher death rate. Our goal is to provide an overview of the clinical spectrum of ischaemic arterial events that may either reveal or complicate COVID-19. Several suspected pathophysiological mechanisms could explain the association between cardiovascular events and COVID-19 (role of systemic inflammatory response syndrome, endothelial dysfunction, activation of coagulation cascade leading to a hypercoagulability state, virus-induced secondary antiphospholipid syndrome). We need additional studies of larger size, to estimate the incidence of these arterial events and to assess the efficacy of anticoagulation therapy.